On the relationship between trade agreements and institutional and political factors - Florensa, Luis Marcelo (2015)
Fil: Florensa, Luis Marcelo. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas. Instituto de Economía y Finanzas; Argentina.